Web-based geoinformation tool for mapping surface water occurrence: a case study of the Dnipro River Delta Ramsar site - Kozlova, Anna; Andreiev, Artem (Ukrainian journal of remote sensing, 2026)
Wetlands are important for ensuring ecological stability and preserving biodiversity, both of which directly affect human well-being. However, these ecosystems have recently been degraded due to climate change and, for Ukraine, by military actions, in particular the destruction of the Kakhovka hydroelectric power station. In such conditions, remote sensing methods are the optimal tool for assessing these changes, as they enable analysis of large areas and the acquisition of up-to-date data even when ground surveys are impossible due to military actions. The paper proposes an approach to assessing the spatiotemporal dynamics of the water surface based on the indicator of its frequency of occurrence (Surface Water Occurrence, SWO), which is used to generate corresponding maps (SWOM). Based on this approach, a web-based geoinformation tool has been developed and implemented on the Google Earth Engine platform, which enables fast processing of large volumes of data without requiring powerful computing resources from the user. The input data are the Dynamic World land cover classification products and the Scene Classification Layer (SCL), which is part of each Sentinel-2 satellite image. This tool allows you to calculate SWOM and classify it into three classes - "No Water", "Temporary Water", and "Permanent Water", as well as obtain statistical indicators of the areas of these classes. The developed tool is cross-platform, so it can be used on different types of devices, including computers, tablets, and even mobile devices. The practical testing of the tool was carried out on the example of the Ramsar site "Dnipro River Delta" for the period 2024–2025. The calculated SWOM maps and the corresponding statistical indicators showed that permanent water surfaces cover 136.14 km² (39.55%), while temporary ones cover 26.81 km² (7.79%) of the total study area. The conducted experiment demonstrates the tool’s capability to analyze the spatial distribution of the water surface. Therefore, the proposed tool can be used to solve applied problems of environmental monitoring, and can also be applied to other study areas. Author Contributions: Conceptualization – A. O. Kozlova and A. A. Andreiev; Methodology – A. A. Andreiev and A. O. Kozlova; Formal Analysis and Data Processing – A. A. Andreiev; Investigation – A. O. Kozlova; Writing – Original Draft Preparation – A. A. Andreiev and A. O. Kozlova; Writing – Review & Editing – A. O. Kozlova and A. A. Andreiev. All authors have read and agreed to the published version of the manuscript. Funding: This research received no external funding. Disclosure of AI use: We confirm that no generative artificial intelligence tools were used in the preparation of this manuscript. Data Availability Statement: Data Availability Statement: The developed web-based geoinformation tool is publicly available at: https://artemaandreev.users.earthengine.app/view/swomdniprodelta. Acknowledgments: The authors are grateful to the National Academy of Sciences of Ukraine for supporting this research. We are also grateful to the reviewers and editors for their valuable comments, recommendations, and attention to the work. Conflicts of Interest: The authors declare no conflict of interest